Psychometric validation of the internet related experiences questionnaire and mobile related experiences questionnaire among Ecuadorian teenagers - Andrade, Livia I.; Viñán-Ludeña, Marlon Santiago; Sanchez, Carmen (Frontiers in Psychology, 2024)
Excessive internet and mobile cell phone use has been increasing in recent years especially in teenagers who are a vulnerable population. However, there is a lack of psychometric evaluation of instruments that allow to identify behavior regarding problematic use of the internet and cell phones in the Latin America, particularly in Ecuador. The main aim of this study is to examine the psychometric properties of two instruments: the Internet-related experiences questionnaire (IREQ) and Mobile-related experiences questionnaire (MREQ) in high school students (n = 4, 174, M age = 15.63; 51.19% male and 48.37% female). The validation process was performed using one and two factors for both questionnaires according to previous literature. After checking the models proposed to date, the best fit model was the one-factor model for (IREQ) and one-factor model for (MREQ). The invariance was performed using two samples according to gender (male, female) and has been confirmed with an acceptable internal consistency for both questionnaires. For IREQ (All, ω = 0.80; Male, ω = 0.77; Female, ω = 0.82) and for MREQ (All, ω = 0.83; Male, ω = 0.82; Female, ω = 0.84). In addition, we performed the correlation analysis between IREQ, MREQ and socio-demographic variables and finally, both instruments demonstrated strong psychometric qualities within the local population.